Pengaruh Penyaluran Kredit dan Restrukturisasi Kredit terhadap Kinerja Non-Performing Loan pada Himbara Selama Pandemi Covid-19 (Periode 2020-2022) - Alfonso Alfonso (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2023)
The Covid-19 pandemic prevention policy in Indonesia has had an influence on economic activity nationally on the performance of the banking sector. The Financial Services Authority issued a policy regarding Credit Restructuring regulations to encourage optimization of banking performance, especially the intermediation function in credit placement in the business sector. The credit risk factor as measured by Non-Performing Loans (NPL) which arose because of policies during the pandemic became a benchmark for banking ability to carry out operational operations. This study aims to see the effect of the indicators of Credit Distribution and Credit Restructuring on NPL Performance during the Covid-19 pandemic. The samples used in this study were four state-owned banks that are members of the Association of State-Owned Banks. This research was conducted using a quantitative approach using time series data for the 2020-2022 period and using the multiple linear regression analysis method to review the effect of Credit Distribution and Credit Restructuring on NPL performance at the Association of State-Owned Banks during the Covid-19 pandemic. The results of this study are that Credit Distribution has a significant negative effect on NPL and Restructured Credit has no significant positive effect on NPL during the Covid-19 pandemic.